Implementasi Pendidikan Multikultural Di Pondok Pesantren Al-Baqiyatush Shalihat Tanjung Ketahanan Nasional Jabung Barat Ikhitar Membangun Ketahanan Nasional - Kasful Anwar Us.; Fathul Anwar (Proceedings of Annual Conference on Islamic Educational Management, 2021)
This paper aims to provide a solution regarding the implementation of multicultural education at the Al-Baqiyatush Islamic Boarding School Shalihat Tanjung Jabung Barat in an effort to build national resilience. The method used is qualitative (qualitative research). The resulting findings indicate that the national resilience of the Indonesian nation is currently fragile due to differences that are not handled properly. Therefore, multicultural education from the Islamic perspective must be a solution to strengthen the Indonesian nation, for that multicultural education is needed that is in accordance with Islamic teachings so that it does not deviate and does not cause unrest. the implementation of multicultural education at the Al-Baqiyatush Islamic Boarding School Shalihat Tanjung Jabung Barat endeavors to build national resilience is through coexistence with the community, tolerance and mutual respect, prioritizing deliberation, promoting brotherhood and togetherness, promoting trust.